2022
DOI: 10.1093/jac/dkac196
|View full text |Cite
|
Sign up to set email alerts
|

Isavuconazole plasma concentrations in critically ill patients during extracorporeal membrane oxygenation

Abstract: Background Isavuconazole is an antifungal drug used for treatment of invasive fungal infections. Critically ill COVID-19 and influenza patients require extracorporeal membrane oxygenation (ECMO) in cases with severe acute respiratory distress syndrome and have risk factors for invasive pulmonary aspergillosis. Little is known about isavuconazole plasma concentrations during ECMO. Objectives To determine isavuconazole plasma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 34 publications
0
16
0
2
Order By: Relevance
“…The use of ECMO in the ICU has been described as possibly playing a role in pharmacokinetic changes in some patients and, particularly with lipophilic and highly protein-bound therapies, that may be captured by the ECMO system [ 59 ]. In the study by Kriegl et al, no difference was found between pre- and post-membrane concentrations, therefore excluding adsorption on the membrane [ 60 ]. The data in the literature are limited concerning isavuconazole and ECMO.…”
Section: Discussionmentioning
confidence: 99%
“…The use of ECMO in the ICU has been described as possibly playing a role in pharmacokinetic changes in some patients and, particularly with lipophilic and highly protein-bound therapies, that may be captured by the ECMO system [ 59 ]. In the study by Kriegl et al, no difference was found between pre- and post-membrane concentrations, therefore excluding adsorption on the membrane [ 60 ]. The data in the literature are limited concerning isavuconazole and ECMO.…”
Section: Discussionmentioning
confidence: 99%
“…The nine ECMO patients included in our study exhibited lower isavuconazole drug levels, which is in line with other reports, 16,28–30 in which a sum of nine ECMO patients had been included. In contrast, one study reported sufficient levels of this drug in seven ECMO patients with prophylactic administration 31 . A mean isavuconazole C min level of 1.09 μg/mL was measured after 24 h. It was discussed that ECMO therapy also increases the volume of distribution which can lower the drug's levels 32,33 …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, one study reported sufficient levels of this drug in seven ECMO patients with prophylactic administration. 31 A mean isavuconazole C min level of 1.09 μg/mL was measured after 24 h. It was discussed that ECMO therapy also increases the volume of distribution which can lower the drug's levels. 32,33 Regarding the influence of RRT on isavuconazole levels, a study with seven solid-organ transplant patients reported no rapid removal by RRT, 34 while others found an association between RRT and sub-therapeutic levels of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Invasive aspergillosis (IA) and mucormycosis are the two most common IMIs in humans and, even when treated appropriately, associated with mortality rates of 30% and above. [5][6][7][8][9][10] Failure of first line treatment, which consists of antifungal treatment and often -especially in the case of mucormycosis -also of surgical debridement, 2,6,11 may occur due to (i) absence of clinical response resulting in refractory or breakthrough fungal infection, [12][13][14] (ii) intolerance/adverse events to first line antifungals, 15 or (iii) insufficient antifungal plasma levels [16][17][18] remaining below defined thresholds for clinical efficacy. [19][20][21] As a consequence, failure of first line antifungal treatment necessitating salvage treatment is quite common.…”
Section: Introductionmentioning
confidence: 99%